Female sex workers perspectives and concerns regarding HIV self-testing: an exploratory study in Tanzania - Soori Nnko; Daniel Nyato; Evodius Kuringe; Caterina Casalini; Amani Shao; Albert Komba; John Changalucha; Mwita Wambura (BMC, 2020)
Abstract Background HIV testing is a gateway to HIV care and treatment for people diagnosed with HIV and can link those with negative results to HIV preventive services. Despite the importance of HIV testing services (HTS) in HIV control, uptake of HTS among female sex workers (FSWs) across sub-Saharan Africa (SSA) remains sub-optimal. Concerns about stigma associated with sex work and fear of loss of livelihood if HIV status becomes known, are some of the restrictions for FSWs to utilize HTS offered through health care facilities. Introduction of HIV self-testing (HIVST) may mitigate some of the barriers for the uptake of HTS. This study explored the acceptability of FSWs towards the introduction of HIVST in Tanzania. Methods We conducted an exploratory study employing in-depth interviews (IDI) and participatory group discussions (PGD) with FSWs in selected regions of Tanzania. Study participants were recruited through snowball sampling. Data were thematically analysed by two analysts using NVivo software. The analysis was informed by the social-ecological model and focused on factors associated with the acceptability of HIVST. Results We conducted 21 PGD sessions involving 227 FSWs. Twenty three IDIs were conducted to complement data collected through PGD. Our study has demonstrated that FSWs are enthusiastic toward HIVST. Convenience (time and cost saved), and belief that HIVST will increase privacy and confidentiality motivated participants' support for the self-testing approach. Participants did express concerns about their ability to interpret and trust the results of the test. Participants also expressed concern that HIVST could cause personal harm, including severe distress and self-harm for individuals with a reactive test. Very likely, concern about adverse effects of HIVST was linked to the study participants' lay perception that HIVST would be provided only through unassisted modality. Conclusions FSWs demonstrated high enthusiasm to use the HIVST once it becomes available. Expectations for increased confidentiality, autonomy, and reduced opportunity costs were among the leading factors that attracted FSWs to HIVST. The major obstacles to the acceptability of HIVST included fear of HIV reactive test and not trusting self-diagnoses. Our findings underscore the importance of providing adequate access to counselling and referral services in conjunction with HIVST.